Survey on Recent Trends in Bio Metrics as Authentication - Vinitha, D; Ramesh, PV (International Journal of Computer Sciences and Engineering, 2025)
In this paper, With the raise of rapid innovation in current biometric technology field, new uses are appearing to make the process of authentication more convenient and secure. These innovative and useful processes of human identification are increasing in frequency with every year. As these users are increasing enormously, they are also creating some trends or ways and restructuring the way we identify humans. Passwords can’t be used that much extensively as they are easily guessed and prone to guess attacks or brute force attacks. Of all the trends we see in the field of biometric technology, most are focused on finding a better and more efficient way of authenticating a person based on “Who they are.” Of course, there are still the traditional ways of identifying a person including personal identification numbers (PINs), ID cards, and passwords but these methods identify a person based on “what they have” or “what they know.” Two Factor Security or Multi factor security measures are quite applicable to some of the domains / ideas. None of them identifies a person with the most important factor, which is “Who they are.” As biometric traits are personal and unique, this is perhaps the most accurate way of identifying a person